2021
DOI: 10.14814/phy2.15119
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved intramuscular inflammation, not diminished skeletal muscle regenerative capacity, is at the root of rheumatoid cachexia: insights from a rat CIA model

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
3
1
0
Order By: Relevance
“…The reduction in TGF- β observed in this study may thus also have resulted in an increase in Id2, contributing to inhibition of differentiation. This is in agreement with a previous rodent collagen-induced arthritis study by our group, where increased Id2 was indeed observed [ 24 ]. This provides additional insight into the occurrence of rheumatoid cachexia despite an increase in myogenic regulatory factors, including myogenin, as reported by our group and others [ 50 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The reduction in TGF- β observed in this study may thus also have resulted in an increase in Id2, contributing to inhibition of differentiation. This is in agreement with a previous rodent collagen-induced arthritis study by our group, where increased Id2 was indeed observed [ 24 ]. This provides additional insight into the occurrence of rheumatoid cachexia despite an increase in myogenic regulatory factors, including myogenin, as reported by our group and others [ 50 ].…”
Section: Discussionsupporting
confidence: 94%
“…These effects were likely the result of various growth factors and cytokines present in the serum stimulating the proliferation of myoblasts and fibroblasts. This aligns with the data observed in the rodent CIA model where increased cellular presence was observed; however, the ratio between the cells did not differ [ 24 ]. While distinguishing between the cells in single culture was possible due to the low desmin/high fibronectin expression in fibroblasts and low fibronectin/high desmin expression in myoblasts, coculture presents some challenges in this regard.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations